(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
This study was carried out to determine the performance of thecounter-poise ‘Shadouf’, which is widely used along Wadi Azum inZalengi area, West Darfur State, Sudan, to irrigate small holdings. Thestudy included data collection on ‘Shadouf’, crop water requirements andsoil characteristics; namely, mechanical analysis and hydraulicconductivity. The results showed that the ‘Shadouf’ has an averagedischarge rate of 1.34 ℓ/s, enough to irrigate an area of 0.22 feddan (1 fed.= 0.42 ha) during winter or 0.18 feddan during summer when the device isoperated for six hours per week.